PENGARUH PENERAPAN AKUNTANSI SEKTOR PUBLIK DAN PENGAWASAN INTERNAL TERHADAP KUALITASS LAPORAN KEUANGAN DINAS PERHUBUNGAN KOTA SEMRANG - Arini Novandalina; Fidyah Yuli Ernawati (Sekolah Tinggi Ilmu Ekonomi Semarang, 2020)
The increasing demands of the community for good government governance, has encouraged the central government and local governments to implement public accountability. This study aims to determine the effect of the application of public sector accounting and internal controls on the quality of the Semarang City Transportation Agency's financial reports. The population in this study were all 124 employees at the Semarang City Transportation Agency. The sample in this study used Cluster Random Sampling, which is a method of sampling by cluster. The population is divided into large sampling units called clusters. The results of this study indicate that the variables of the application of public sector accounting, internal control on the quality of financial reports have a positive and significant effect on the performance accountability of government agencies. This is indicated by the results obtained from the partial test (t test) for variable X1 with a value of 2.287> 1.96 with a significance of 0.037 <0.05 and for variable X2 with a value of 2.647> 1.96 with a significance of 0.012 <0.05. This means that if the public sector accounting reporting standards and supervision of the quality of financial reports can be improved, it will produce good accountability performance. The conclusion of this study is that the application of public sector accounting and internal supervision has a positive effect on the quality of financial reports, this indicates that the higher the application of public sector accounting and internal controls, the higher the quality of financial reports